Out of control: Evidence for anterior insula involvement in motor impulsivity and reactive aggression - Dambacher, Franziska (Soc Cogn Affect Neurosci, 2015)
Inhibiting impulsive reactions while still defending one’s vital resources is paramount to functional self-control and successful development in a social environment. However, this ability of successfully inhibiting, and thus controlling one’s impulsivity, often fails, leading to consequences ranging from motor impulsivity to aggressive reactions following provocation. Although inhibitory failure represents the underlying mechanism, the neurocognition of social aggression and motor response inhibition have traditionally been investigated in separation. Here, we aimed to directly investigate and compare the neural mechanisms underlying the failure of inhibition across those different modalities of self-control. We used functional imaging to reveal the overlap in neural correlates between failed motor response inhibition (measured by a go/no-go task) and reactive aggression (measured by the Taylor aggression paradigm) in healthy males. The core overlap of neural correlates was located in the anterior insula, suggesting common anterior insula involvement in motor impulsivity as well as reactive aggression. This evidence regarding an overarching role of the anterior insula across different modalities of self-control enables an integrative perspective on insula function and a better integration of cognitive, social and emotional factors into a comprehensive model of impulsivity. Furthermore, it can eventually lead to a better understanding of clinical syndromes involving inhibitory deficits.